Transforming collaboration between communities and non-governmental organisations: Reflections on learning spaces in Central-Eastern Uganda - Blaak, Marit; Irepu, Sophia; Zeelen, Jacques (SAGE Publications, 2024)
Non-governmental organisations have several mechanisms in place to facilitate learning with and from communities they intend to serve, however these do not always realise authentic participation and meaningful programmatic adjustments. In a participatory research in Central-Eastern Uganda we investigated how the community believes collective learning with NGOs could best be shaped. In this paper we present findings as well as reflections on the learning spaces that emerged in the research and how one could assess whether collective learning is a transformative practice. We offer a conceptual framework NGO practitioners can use to enrich their collective learning toolkit as well as to track and trace small shifts and changes happening in learning trajectories in order to lobby for resources to allow collective learning to happen more authentically, through increased presence and informal interaction with communities.
Keywords: Uganda, non-governmental organisations, participatory development, action science, youth development